Effects of an Intranet-Based Call-for-Help System on Teamwork, Work Efficiency, Job Satisfaction, and Job Stress in Nurses. Issue 6 (30th September 2022) - Tai, Jui-Fen; Yang, Tsung-Lung; Juang, Wang-Chuan; Lin, Li-Ying
Abstract : Objectives: In the medical environment, teamwork among medical care personnel is closely related to patient safety and care quality. This research has developed an Intranet-based call-for-help system to establish an emergency support system. Few studies have explored the effects of the timely call-for-help system on teamwork. This study explored the effects of the timely call-for-help system intervention. Methods: This study was designed by 2 groups of pretest and posttest. This research was conducted at a medical center in Taiwan. The subjects of the study were nurses in inpatient wards. The newly established call-for-help system was used in the 4 experimental wards, enabling nurses to immediately seek help from each other when faced with challenges and difficulties. This study was blind with the outcome evaluator and data analyst blinded to the group of participants. Results: A total of 165 nurses were included in the study, 84 in the intervention group and 81 in the control group. After the intervention of the call-for-help system, the experimental group had significantly better teamwork, work efficiency, job satisfaction, and lower job stress than the control group ( P < 0.01). The generalized estimating equation showed that the progress scores of the experimental group on the 4 scales were significantly higher than those of the control group ( P < 0.01). Conclusions: The implementation of timely call-for-help system can enable nursing staff to get immediate support, strengthen teamwork, create a positive nursing practice environment, and improve patient safety and quality of care. These improvements in teamwork and support are very important and worthy of promotion.